PENGARUH PEMBELAJARAN BERBASIS MULTIMEDIA DAN GAYA KOGNITIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Rini Daraini (Jurnal Teknologi Pendidikan (JTP), 2012)
Abstract: The aim of this research is to find out: (1) the significance of problem solving capability in mathematics of the students taught with interactive multimedia based-instruction in comparison with those taught with linear multimedia based-instruction; (2) the different of problem solving capability between the students with impulsive cognitive style and those with reflective cognitive style; and (3) the interaction of multimedia based-instruction and cognitive style in determining the capability of the students in problem solving in Math. The finding of the research shows that: (1) the students’ capability of problem solving taught with interactive multimedia (= 27.78) is higher that those taught with linear multimedia (= 26.48), with Fcount = 4.92 > Ftable = 3.92, (2) the students’ ability of problem solving who poses impulsive cognitive style (= 26.11) is lower than those who poses reflective cognitive style (= 28.16), with Fcount = 23.13 > Ftable = 3.92, (3) there is interaction between multimedia based-instruction and cognitive style towards students’ ability in Mathematic problem solving, with Fcount = 29.57 > Ftable = 3.92.   Keywords: Problem solving capability, Multimedia based learning, Cognitive style.